Digital Extended Man Looking for His Wholeness - G.U. Soldatova; S.N. Ilyukhina (Культурно-историческая психология)
The mixed online-offline reality, with the technosystem as an integral component of the digital era's ecological human system, has given rise to a new anthropological type: the technologically augmented human, enhanced by digital tools. This extended human, simultaneously embodied in the physical realm and dematerialized through extra-corporeal expansion, becomes distributed across multiple realities and digital spaces. This distribution challenges the concept of holistic subjectivity. The problem of wholeness is examined through technological, cognitive, motivational-value, and socio-behavioral dimensions. A key focus is on identifying new methods for managing digital extensions, fostering internal coherence, and integrating digital and real-world identities to enable conscious, responsible, effective, and safe participation in digital social practices. In this era of rapid digital transformation, the wholeness of modern humans must be reevaluated based on a fundamental principle: a changing individual exists within a constantly transforming world. This principle acknowledges the limitations of previous anthropological frameworks and norms in understanding humanity, recognizing humans as an open, unfinished project perpetually striving to realize their boundless potential.